Balkan Reunion/Pub(lic) Conference : May 28 - 31, 2004. - Institute of Contemporary Art, Sofia (Sofia : Institute of Contemporary Art, 2005)
Angelov, Angel ; Block, Rene ; Boubnova, Iara ; Boyadjiev, Luchezar ; Carras, Maria-Thalia ; Djuric, Uros ; Gemisheva, Mariela ; Genova, Yana ; Gospodinov, Georgi ; Ilic, Natasa ; Kabakchieva, Petya ; Dimitar, Kambourov ; et al.
Institute of Contemporary Art, Sofia, May 28 - 31, 2004
boek
Keywords: Balkan